Needs of Patients with Opioid Dependence: Are the Perspectives of Substance Use Disorder – Patients and their Family Caregivers Similar? - Denny Mariam Oomen; Sandhya Gupta; Siddharth Sarkar; Y. Surbala Devi (Indian Journal of Psychiatric Nursing)
Context: There are more than ten thousand opioid-dependent patients visiting the study setting annually, depicting the serious public health issue associated with opioid use. The upheaval in all phases of life of a patient necessitates active involvement of both patient and caregiver. The importance of need assessment of patient by patients themselves and their caregivers need to be separately assessed to provide holistic care to patients. Aim: The aim of the study was to assess the needs of patients with opioid dependence syndrome as perceived by patients themselves and their family caregivers. Setting and Design: A comparative cross-sectional study conducted in a drug dependence treatment facility in India. Subjects and Methods: The needs of 105 opioid-dependent patients perceived by patients themselves and their family caregivers were assessed using Camberwell Assessment of Need Short Appraisal Schedule. Results: The most common unmet needs of patients as rated by patients themselves were physical health, money, and company. The most common unmet needs of patients rated by caregivers were money, looking after home and daytime activities. The agreement of needs of patient was poor in domains such as self-care (k = 0.17), looking after home (k = 0.16), company (k = 0.13), physical health (k = 0.10), money (k = 0.09), and psychological distress (k = 0.06). Conclusion: Addressing the needs of patients with opioid dependence might help in developing a more holistic management plan which will improve treatment outcomes. Nurses should be active part of communication system and fill the gap existing in the needs of patients.